PERAN POLITIK PEREMPUAN DALAM KACAMATA ICT - Roqib, Moh. (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2008)
This paper will discuss woman’s politic role, political leadership viewed as difficult task, and womandeemed as incapable. At this point, ICT or multimedia can effectively help woman’s political task. Sophisticated andenhanced information technology and communication can simplify leader task and duty. Through ICT, leader cangive commando, dividing task, motivate, and giving punishment quickly and easily. ITC make everything easy,fast, with high quality. Computerization and digitalization positioned woman equal with man, as long as knowledgeand technological capability equal too. Physical constraint is not a problem for one that technology-literate. The lastquestion is about quality, only depend on it man and woman have equal chance to success and leading the world